2021
DOI: 10.3389/fonc.2021.619599
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms Forecasting Long-Term Overall and Cancer Specific Survival of Patients With Head and Neck Neuroendocrine Carcinoma

Abstract: BackgroundThe purpose of this retrospective analysis was to build and validate nomograms to predict the cancer-specific survival (CSS) and overall survival (OS) of head and neck neuroendocrine carcinoma (HNNEC) patients.MethodsA total of 493 HNNEC patients were selected from the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and 2015, and 74 HNNEC patients were collected from the Affiliated Cancer Hospital of Xiangya School of Medicine, Central South University/Hunan Cancer Hospital (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In contrast, Gnepp et al [52] reported that 90% of patients with poorly differentiated laryngeal NEC would experience a metastasis at some point in their illness, most likely to the cervical lymph nodes, liver, lung, or bone [52]. More recently, Yan et al [53] studied 493 head and neck NEC individuals, and almost 80% of them had distant metastases [53]. On this basis, we may infer that OMNEC may exhibit a lower potential metastasis rate than other anatomical locations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Gnepp et al [52] reported that 90% of patients with poorly differentiated laryngeal NEC would experience a metastasis at some point in their illness, most likely to the cervical lymph nodes, liver, lung, or bone [52]. More recently, Yan et al [53] studied 493 head and neck NEC individuals, and almost 80% of them had distant metastases [53]. On this basis, we may infer that OMNEC may exhibit a lower potential metastasis rate than other anatomical locations.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the prognosis of HNMM patients is better than that of patients with other malignancies in the head and neck region (25,26). According to the largest case series reported to date, the 5-year cumulative survival rate of 59 Chinese patients with HNMM was 62% (27).…”
Section: Discussionmentioning
confidence: 99%